Self-esteem, job insecurity, and psychological distress among Chinese nurses - Yun Liu; Chunyan Yang; Guiyuan Zou (BMC, 2021)
Abstract Background Many studies investigate the variables relating to psychological distress among nurses, but little is known about the underlying mechanism(s) among job insecurity, self-esteem, and psychological distress. Aims This cross-sectional study examines the prevalence of psychological distress among nurses and the relationships among job insecurity, self-esteem, and psychological distress; it also explores how self-esteem might mediate between job insecurity and psychological distress. Methods Questionnaires that assess job insecurity, self-esteem, and psychological distress were collected from 462 nurses in a tertiary hospital in Shandong Province, China. Results Our results show an 83.3 % prevalence rate for psychological distress among nurses. Regression analysis results show that job insecurity positively correlates with psychological distress, explaining 17.5 % of the variance in psychological distress. Mediation analysis results show that self-esteem partially mediates the effect of the two dimensions of job insecurity on psychological distress. Conclusions Psychological distress is prevalent among Chinese nurses. Nursing administrators should take effective measures to improve self-esteem and reduce the negative impacts of job insecurity on nurses, including psychological distress.